Demonstration of a three compartment solar electrolyser with gas phase cathode producing formic acid from CO2 and water using Earth abundant metals - Thijs, Barbara; Hanssens, Lucas; Heremans, Gino; Wangermez, Wauter; Rongé, Jan; Martens, Johan A. (Frontiers in Chemical Engineering, 2022)
A three compartment solar formic acid generator was built using a Sn on Cu foam cathode and NiFe anode. A bipolar combination of a Fumasep FAD-PET-75 and Nafion 117 membrane was mounted between anode and middle compartment, which was filled with Amberlyst 15H ion exchanger beads. A Fumasep FAD-PET-75 membrane separated the middle compartment from the cathode. The generator was powered with a photovoltaic panel and fed with gaseous CO2 and water. Diluted formic acid solution was produced by flowing water through the middle compartment. Common PV-EC devices are operated using aqueous electrolyte and produce aqueous formate. In our PV-EC device, formic acid is produced straight away, avoiding the need for downstream operations to convert formate to formic acid. The electrolyser was matched with solar photovoltaic cells achieving a coupling efficiency as high as 95 %. Our device produces formic acid at a faradaic efficiency of ca. 31 % and solar-to-formic acid efficiency of ca. 2 %. By producing formic acid from CO2 and water without any need of additional chemicals this electrolyser concept is attractive for use at remote locations with abundant solar energy. Formic acid serves as a liquid renewable fuel or chemical building block.